PMO-032 Validation of a food frequency questionnaire for estimating calcium intake in young female adults. (28th May 2012) - Cawley, R; Mackenzie-Fraser, M
Abstract : Introduction: The relatively low cost and low respondent burden of a Food Frequency Questionnaire (FFQ) that effectively and rapidly identifies individuals with low calcium intakes would be a valuable asset to clinical dietetics. Young female adults (age 18–30 years) tend to have a lower calcium intake which may increase their risk of osteoporosis in later life. This study aimed to examine the validity and reliability of a non-quantitative calcium FFQ by comparing the mean calcium intake measured by the FFQ with that measured by a 7 day weighed food diary. Methods: The validity and reliability of non-quantitative calcium FFQ was evaluated. A self-administered FFQ was administered to 41 Caucasian female participants, aged 18–26 years, studying at the Robert Gordon University, Aberdeen. A points system was used to assess whether the individual was meeting their recommended calcium requirement. A paired t test measured the difference between the mean calcium intake measured by the food diary and the FFQ. Results: The mean calcium intake estimated by the FFQ and the 7 day weighed food diary was 622.0±138.3 mg/day and 692.5±188.1 mg/day, respectively. A paired t test revealed a significant difference of 70.6±78.1 mg/day between the calcium intake measured by the FFQ and the food diary ( P r=0.931, p < 0.05) Conclusion: A small but significant difference of 70 mg/day was found between the calcium intake measured by the FFQ and the 7-day food diary. However, this significant result did not reflect the precision between the two methods at estimating calcium intake. Both Pearson's correlation coefficient and Bland Altman procedures demonstrated good agreement and validity. The FFQ identified individuals with low calcium intakes; however, the degree of underestimation by the FFQ increased when calcium intake increased. Although the FFQ may not be as accurate as a 7-day weighed food diary when estimating absolute calcium intake it appears to be an effective method of rapidly identifying individuals with low calcium intake. This easily utilised calcium FFQ could be a valuable and useful clinical tool in identifying individuals with calcium deficient diets. Furthur research into whether this FFQ is a reliable method of identifying low calcium intakes in other subgroups of the population is recommended. Competing interests: None declared. References: 1. Bates B, Lennox A, Swan G. National diet and nutrition survey. London: Department of Health, 2009. 2. Salvini S, et al. Food-based validation of a dietary questionnaire: the effects of week-to-week variation in food consumption. Int J Epidemiol 1989;18 :858–67. 3. Tefft M, Boniface D. Estimating food and nutrient intake from food frequency questionnaire data by reference to a standard weighed diet survey. J Hum Nutr Diet 2000;13 :219–24.